Give and You Shall Receive: The Emergence of Welfare-Reducing Reciprocity - Cameron K. Murray; Paul Frijters; Melissa Vorster (Institute for the Study of Labor (IZA), 2015)
We develop a new experiment to study the emergence of welfare-reducing bilateral alliances within larger groups, and the effectiveness of institutional interventions to curtail this reciprocal alliance behaviour. In each of the 25 rounds of our experiments, a player (the 'allocator') nominates one of three others as a co-worker (the 'receiver'), which deter- mines the group production that period to be the productivity of the receiver (which varies by round), but also gives the receiver a bonus and makes them the allocator in the next round. Alliances then form if two individuals keep choosing each other even when their productivities are lower than that of others, causing efficiency losses. Males and business students are found to be more likely to form welfare reducing alliances. Random allocator rotation policies and low bonuses fail to significantly improve overall welfare: rotation policies significantly reduce the rate of formation of new alliances but do not lead to the breakdown of existing alliances, while low bonus policies are only found to be effective when alliances are well established. This points to the importance of the strength of existing alliances for the chances of institutional interventions curtailing welfare reducing reciprocity, i.e. 'back-scratching'.
Keywords: D71; D72; D63; 330; reciprocity; corruption; alliance formation; experiment